2022
DOI: 10.48550/arxiv.2211.03246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A giant glitch from the magnetar SGR J1935+2154 before FRB 200428

Abstract: Fast radio bursts (FRBs) are short pulses observed in radio frequencies usually originating from cosmological distances. The discovery of FRB 200428 and its X-ray counterpart from the Galactic magnetar SGR J1935+2154 suggests that at least some FRBs can be generated by magnetars. However, the majority of X-ray bursts from magnetars are not associated with radio emission. The fact that only in rare cases can an FRB be generated raises the question regarding the special triggering mechanism of FRBs. Here we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
(78 reference statements)
1
3
0
Order By: Relevance
“…Such a situation could appear in the global activity of a magnetar due to a conversion of the magnetic field from a dipolar to a multipolar configuration (e.g., the situation considered in Yang & Zhang 2021). Here, it is interesting to mention that a giant glitch occurred approximately 3 days before FRB 20200428, as reported recently by Ge et al (2022). The occurrence of the glitch means the magnetar crust had just obtained a sudden increase of the angular momentum, which could have been transferred from the core of the magnetar.…”
Section: Conclusion and Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Such a situation could appear in the global activity of a magnetar due to a conversion of the magnetic field from a dipolar to a multipolar configuration (e.g., the situation considered in Yang & Zhang 2021). Here, it is interesting to mention that a giant glitch occurred approximately 3 days before FRB 20200428, as reported recently by Ge et al (2022). The occurrence of the glitch means the magnetar crust had just obtained a sudden increase of the angular momentum, which could have been transferred from the core of the magnetar.…”
Section: Conclusion and Discussionsupporting
confidence: 63%
“…On 2020 April 28, from the direction of a Galactic magnetar, SGR J1935+2154, the Canadian Hydrogen Intensity Mapping Experiment (CHIME) captured a fast radio burst (FRB) emission (Bochenek et al 2020;CHIME/FRB Collaboration et al 2020), which was precisely temporally associated with an X-ray burst (XRB; Li et al 2021Li et al , 2022aGe et al 2022). This magnetar had just entered an active state of XRB about half a month before FRB 20200428 occurred (Barthelmy et al 2020;Lin et al 2020a;Mereghetti et al 2020;Ridnaia et al 2020Ridnaia et al , 2021Tavani et al 2020;Veres et al 2020;Younes et al 2020;Kaneko et al 2021;Li et al 2021;Cai et al 2022aCai et al , 2022b and remained active at other times as well (Israel et al 2016;Lin et al 2020b;Borghese et al 2022;Xie et al 2022;Rehan & Ibrahim 2023;Xie et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Also because the long time span of our study, none of the existing ephemeris can fully cover all the bursts. The ephemeris used in this paper is fitted results based on the combined ephemeris evolution data derived from NuSTAR, NICER and XMM-Newton in (Ge et al 2022), which yield f = 0.30794447(1) Hz,  f 2.165 10 Hzs 12 1…”
Section: X-ray Pulse Profile Analysis Based On Insight-hxmt Le Datamentioning
confidence: 99%
“…Subsequently, three FRB-like radio bursts emitted from SGR J1935+2154 were detected by the CHIME/ FRB system on 2020 October 8 (Good & Chime/Frb Collaboration 2020). More surprisingly, Ge et al (2022) utilized the observations from NICER, NuSTAR, Chandra, and XMM-Newton to study the timing properties of SGR J1935 +2154 around the epoch of FRB 20200428, and reported that a giant spin-up glitch with Δν = 19.8 ± 1.4 μHz occurred approximately 3.1 ± 2.5 day before FRB 20200428.…”
Section: Introductionmentioning
confidence: 99%